Textbook of organic medicinal and pharmaceutical chemistry - Jaime N.,ed. Delgado
Physicochemical properties in relation to biological action. Metabolic changes of drugs and related organic compounds. Drug latentiation and prodrugs. Biotechnology and drug discovery. Fundamentals of immunology and immunizing biologicals(vaccines and toxoids). Anti-infective agents. Sulfonamides, sulfones, and folate reductase inhibitors with antibacterial action. Antimalarials. Antibacterial antibiotics. Antiviral agents. Antineoplastic agents. Agents for Diagnostic Imaging. Central nervous system depressants. Central nervous system stimulants. Adrenergic agents. Cholinergic drugs and related agents. Diuretics. Cardiovascular agents. Local anesthetic agents. Histamine and antihistaminic agents. Analgesis agents. Steroids and therapeutically related compounds. Prostaglandins, leukotrienes, and other eicosanoids. Carbohydrates. Amino acids, proteins, enzymes and peptide hormones. Vitamins and related compounds.